Evapotranspiration of ‘Roxo de Valinhos’ fig under different mulches in the Cerrado-Amazon transition - Pizzatto, Mariana; Campelo Junior, José Holanda; Silva, Andréa Carvalho da; Carneiro, Samuel Silva; Debastiani, Matheus Marangon; Souza, Adilson Pacheco de (Comunicata Scientiae, 2024)
Finding out subsidies for the production of perennial fruit trees in the northern region of Mato Grosso, were determined the crop evapotranspiration (ETc), crop coefficients (Kc) and water use efficiency of fig plants 'Roxo de Valinhos', cultivated under different soil mulches in the Cerrado-Amazon transition. The cultures were carried out in two consecutive dry seasons (2020 and 2021), using 2.5 kg m-2 of straw (vegetable waste) of Congo grass 'Brachiaria ruzziensis' (BR), velvet bean ‘Mucuna pruriens L’ (MP), pigeon pea ‘Cajanus cajan L.’ (CC) and zoysia grass ‘Zoysia japonica’ (ZJ) and bare soil ‘without mulch’ (BS). The ETc was obtained by soil water balance through tensiometry. The reference evapotranspiration (ETo) was obtained by the method of Penman Montheit Fao 56, with the crop coefficients given by the ratio between ETc and ETo. The efficiency of water use was established by the ratio between the mass of fruits produced per unit volume of applied water (m³), taking into account the irrigated depth and the effective rainfall. The different mulches not influence the water needs of the fig plants, however, the ETc and Kc were higher when the plants had a greater number of productive branches. The use of mulch increased the efficiency of water use, regardless of the production cycle. The BR and BS mulch crops, in the second year (eight branches), produced 2.59 and 0.79 kg of rip fruit figs per m3 of water depth, respectively.